2014
DOI: 10.1080/10911359.2014.897112
|View full text |Cite
|
Sign up to set email alerts
|

Looking Back and Thinking Forward: Examining the Consequences of Policies and Practices That Treat Juveniles as Adults

Abstract: This article examines the consequences of legislative changes that eased the process of treating juveniles as adults. Overall, it finds evidence that there has been an increase in the number of juveniles sent to the criminal court and the majority either remain in the community or return to the community shortly after serving a jail or prison sentence. In light of geographic and racial/ethnic disparities in transfer, differences in the programs and services offered to youth in the juvenile and criminal justice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Moreover, those who commit offenses as justice-involved youth typically have the option of expunging their records, which is much less frequent in the adult justice system (Jacobs, 2015). Youth in adult facilities tend to receive more disciplinary violations than offenders in juvenile settings because of their inability to navigate through adult time and the punitive environment, thus increasing the chances of solitary confinement, extending their jail time, and perpetuating a cycle of failure that has deleterious, long-term effects on the development of the youth (Fagan, 2008;Redding, 2003;Shook, 2014).…”
Section: Recidivism Rates and Education Outcomesmentioning
confidence: 99%
“…Moreover, those who commit offenses as justice-involved youth typically have the option of expunging their records, which is much less frequent in the adult justice system (Jacobs, 2015). Youth in adult facilities tend to receive more disciplinary violations than offenders in juvenile settings because of their inability to navigate through adult time and the punitive environment, thus increasing the chances of solitary confinement, extending their jail time, and perpetuating a cycle of failure that has deleterious, long-term effects on the development of the youth (Fagan, 2008;Redding, 2003;Shook, 2014).…”
Section: Recidivism Rates and Education Outcomesmentioning
confidence: 99%
“…The study also found that Black juveniles with a history in the juvenile justice system contributed to their increased likelihood of being sentenced to prison time instead of jail, while it reduced the probability of the same for White juveniles. Shook (2014) found that there were major racial differences when it came to the decision to treat juveniles as adults and Black youth were more likely than White youth to be transferred to the adult system. Further, Brown and Sorenson (2013) found that race and gender impacted the decision of juvenile cases waived to adult court.…”
Section: Racial Disparities In Us Juvenile Justice Systemmentioning
confidence: 99%